Contextual Learning Animation Video for Science Subject Content in Grade IV Elementary School - Pasaribu, Noni Linzilah Mona; Suartama, I Kadek; Sukmana, Adrianus I Wayan Ilia Yuda (Jurnal Media dan Teknologi Pendidikan, 2025)
The low student learning outcomes indicate the need for innovative instructional media that can enhance students' motivation and understanding. This study aims to: (1) design and develop a contextual-based interactive animated video as a learning medium for the topic "Moving Energy"; (2) assess the validity of the media; and (3) examine the effectiveness of the media on student learning outcomes. This research is a development study (R&D) employing the ADDIE model. Validity data were collected through expert reviews by content, instructional design, and media experts, as well as individual, small group, and field trials. Effectiveness data were obtained from students’ pre-test and post-test scores and analyzed using a paired t-test. The validity results showed that the media was highly feasible, with the following percentages: content expert 94.12%, instructional design expert 94.60%, and media expert 97.50%; individual trial 96.00%, small group trial 96.89%, and field trial 95.03%. The effectiveness test revealed a highly significant improvement in learning outcomes, with an average difference of -53.409, t-value of -88.224, and significance level of 0.00 (p < 0.05). These findings imply that contextual-based interactive animated video media can serve as an alternative solution to enhance the quality of IPAS learning in elementary schools.